Why self-talk is effective? Perspectives on self-talk mechanisms in sport - Galanis, E.; Hatzigeorgiadis, A.; Zourbanos, N.; Theodorakis, Y. (Sport and exercise psychology research: From theory to practice, 2016)
Self-talk interventions have proven effective for enhancing performance. Identifying the mechanisms underlying the effectiveness of self-talk strategies is now among the top priorities for a comprehensive understanding of the self-talk phenomenon. The present chapter aims at providing an overview of the existing literature and guidance for further research developments on the self-talk mechanisms. First, evidence from self-talk interventions that stress the importance of studying the self-talk mechanisms will be summarized. Subsequently, preliminary evidence and existing conceptual models on the self-talk mechanisms will be presented. Finally, theoretical frameworks that can be adopted to accommodate findings pertaining to the self-talk mechanisms will be identified, and relevant empirical evidence will be presented to support a prospective model of self-talk mechanisms in sport. (übern.)